Why does portfolio choice correlate across generations? - Samuli Knüpfer; Elias Rantapuska; Matti Sarvimäki (Bank of Finland, 2017)
We find that investors tend to hold the same securities as their parents. Instrumental variables that exploit social networks and a natural experiment based on mergers allow us to attribute the security-choice correlation to social influence within families. This influence runs not only from parents to children, but also in the opposite direction. Security holdings correlate more when family members are more likely to communicate and when they are more susceptible to social influence. The identical security holdings that social influence generates largely explain why risk-return profiles of household portfolios correlate across generations.
URN:NBN:fi:bof-201709011589
Keywords: G11; D63; 330